Analisis Penerapan Asas Hukum Pada Perjanjian Sektor Jasa Konstruksi - Kaharuddin, Kaharuddin; Salle, Salle; Saleh, Ahmad (Program Pascarajana Universitas Muslim Indonesia, 2024)
Tujuan penelitian menganalisis penerapan berbagai asas hukum perjanjian dalam berbagai perjanjian jasa konstruksi yang dikemas dalam bentuk perjanjian baku (standad contract). Metode penelitian yang adalah tipe penelitian hukum normative (doctrinal) Hasil penelitian, (1). Asas-asas yang harus terealisasi atau terjabarkan pada perjanjian atau kontrak pada sektor jasa konstruksi yakni: Asas konsensualisme, kebebasan berkontrak, asas kekuatan mengikat perjanjian (pacta sun servanda), asas itikat baik, asas kepercayaan, asas personalia, asas persamaan hukum, asas keseimbangan, asas kepastian hukum, asas kepatutan, asas kebiasaan, asas perlindungan, asas keadilan, asas kepatutan, asas kemanfaatan, dan asas moral. (2). Bahwa beberapa asas-asas perjanjian belum terealisasi atau terjabarkan secara optimal pada berbagai perjanjian atau kontrak pada sektor jasa konstruksi yakni asas kebebasan berkontrak, asas persamaan hukum, asas kepatutan, asas moral dan asas keseimbangan. The research objective is to analyze the application of various legal principles of agreement in various construction service agreements which are packaged in the form of standard contracts. The research method is a type of normative (doctrinal) legal research. Research results, (1). The principles that must be realized or described in agreements or contracts in the construction services sector are the principle of consensual, freedom of contract, the principle of the power of binding agreements (pacta sun servanda), the principle of good faith, the principle of trust, the principle of personnel, the principle of legal equality, the principle of balance, the principle of legal certainty, the principle of propriety, the principle of custom, the principle of protection, the principle of justice, the principle of propriety, the principle of expediency, and the principle of morals. (2). That several principles of agreement have not been realized or explained optimally in various agreements or contracts in the construction services sector, namely the principle of freedom of contract, the principle of legal equality, the principle of propriety, the moral principle and the principle of balance